Analysis of the Radiation Hazard Observed by RAD on the Surface of Mars During the September 2017 Solar Particle Event. Issue 12 (29th June 2018) - Zeitlin, C.; Hassler, D. M.; Guo, J.; Ehresmann, B.; Wimmer‐Schweingruber, R. F.; Rafkin, S. C. R.; Freiherr von Forstner, J. L.; Lohf, H.; Berger, T.; Matthiae, D.; Reitz, G.
Abstract: We report dosimetric quantities measured by the Mars Science Laboratory Radiation Assessment Detector (RAD) on the surface of Mars during the 10–12 September 2017 solar particle event. Despite 23 g/cm 2 of CO2 shielding provided by the atmosphere above RAD, dose rates rose above background galactic cosmic ray levels by factors of 2 to 3 over the course of several hours and leveled off at sustained peak rates for about 12 hr before declining over the following 36 hr. As the solar particle event flux was gradually declining, a shock front reached Mars and caused a sudden drop of about 15% in instantaneous dose rates. No solar particles followed the shock arrival, and the magnetic shielding of galactic cosmic rays by the shock reduced their intensity to levels below those seen before the start of the event. This event is the largest seen to date by RAD on Mars. Plain Language Summary: We report the radiation dose rate on the surface of Mars measured by the Radiation Assessment Detector (RAD) aboard the Curiosity rover before, during, and after the solar energetic particle (SEP) event of 10–12 September 2017. Future astronauts exploring Mars will be at risk from SEP events, which occur sporadically and often with little warning, as well as from galactic cosmic rays, which are a continuous source of radiation dose and which generally have higher energies than SEPs. The event described here was the largest so far observed by RAD in more than five years on Mars. Although the atmosphere of Mars is only about 1–2% as thick as Earth's, it provides a measure of shielding against solar particles, most of which are protons with energies insufficient to penetrate Mars' atmosphere and reach the surface. But in this event, RAD saw a clear increase in dose rates; the peak dose rate was nearly three times above galactic cosmic ray levels measured prior to the event. Though the increase was rapid and lasted for three days, it was too small to represent a risk to the health of an astronaut receiving it. Much larger SEP events are possible and could cause problematic doses. Key Points: Protons accelerated during the large solar particle event of September 2017 reached the surface of Mars and were observed by MSL‐RAD Dose rates were seen to increase by factors of 2 to 3 above the background level of the galactic cosmic rays Doses integrated over a 30‐day interval that included the event remained well below NASA radiation exposure limits for astronauts